Implementation of Working Mother Parenting in Shaping Early Childhood Independence - Rubiah, Siti Agustiani; Patilima, Hamid (Journal of Childhood Development, 2024)
Each parent certainly has a different application of parenting patterns in fostering independent behavior in children. The parenting patterns of working mothers and non-working mothers will certainly be different. One of the results of parenting patterns will be seen from children's independence when participating in school activities. This study was conducted to observe working mothers' parenting patterns in forming an attitude of independence in children at an early age. This research method uses a qualitative method with a phenomenological approach. The study was conducted at the RA Al-Istiqomah Institution, GSI, and involved five informants who were working mothers and guardians of children aged between 4 and 6 years. The results of this study indicate that the application of parenting patterns carried out by working mothers in forming the independence of early childhood children, namely: parents/working mothers are wise in implementing rules and appreciating good behavior, involving children in certain things, always being responsive to children's attitudes, always appreciating and respecting children's thoughts, feelings, involving children in decision making. Meanwhile, the independence reflected in children left by their mothers outside the home includes, the child's physical independence ability, the child's self-confidence, the child's sense of responsibility, the child's ability to be disciplined, ability to be good at socializing, being able to share, the child's emotional control develops very well and develops according to expectations.